2020
DOI: 10.1080/1478422x.2020.1762385
|View full text |Cite
|
Sign up to set email alerts
|

Development of long-term localised corrosion of cast iron pipes in backfill soils based on time of wetness

Abstract: Parameters characterising the properties of soils used as backfill in immediate contact with cast iron pipes exhumed from a variety of soils after up to 129 years exposure are used together with average annual precipitation to estimate the average time of wetness. This is shown to correlate closely with pipe wall corrosion penetration. The possibility of microbiologically influenced corrosion is dismissed owing to lack of critical nutrients. The presence of chlorides in some soils most likely arises from pipe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Soil samples are collected from locations closer to the pipe for in-situ testing or lab characterisation. There are a number of parameters in soil characterisation as shown in Table 1 that can be considered for the assessment of the buried pipe [7,120,121]. Soil characterisation of the surrounding soil of buried pipeline allows the maintenance professionals to take protective measures to prevent or stop any loss of containment [122].…”
Section: Soil Characterisationmentioning
confidence: 99%
“…Soil samples are collected from locations closer to the pipe for in-situ testing or lab characterisation. There are a number of parameters in soil characterisation as shown in Table 1 that can be considered for the assessment of the buried pipe [7,120,121]. Soil characterisation of the surrounding soil of buried pipeline allows the maintenance professionals to take protective measures to prevent or stop any loss of containment [122].…”
Section: Soil Characterisationmentioning
confidence: 99%
“…Studies have shown that about 70 percent of the total global water pipes are buried underground, and most of these pipes have been in service for more than a century [1]- [3]. Due to their critically ageing conditions, these water pipes' failures have been frequently occurring, which cause severe implications for not only sustainability and efficacy of water services but also the living conditions of civilians in surrounding areas including property damages, traffic accidents and obstruction and water supply disruption [4].…”
Section: Introductionmentioning
confidence: 99%